ANALISIS DETERMINAN KEMISKINAN DI 34 PROVINSI DI INDONESIA - Wirayudha, Ariq Bima; Prasetyia, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research examines the issue of poverty in developing countries, particularly in Indonesia, with a focus on understanding the phenomenon of poverty and the influence of determinant variables on the level, depth, and severity of poverty. The study will use panel data regression to identify determinants of poverty. The results of the research indicate that the level of poverty, the poverty depth index, and the severity of poverty have different determinants. Gross Domestic Product (PDRB) and Human Development Index (IPM) have a negative effect on overall poverty, suggesting that efforts to reduce poverty would be effective by increasing PDRB and IPM. On the other hand, Total Population and Inflation have a positive impact on the poverty index. Therefore, policies focused on reducing unemployment and maintaining inflation rates would be essential in efforts to reduce poverty. In conclusion, the findings suggest that addressing specific determinants is crucial in developing targeted policies for poverty reduction.